Los créditos y los depósitos del sistema financiero de Loreto después de la pandemia COVID 19 periodo 2020 - Cubas Angulo, Ericka Camila (2021)
Typically, financial intermediaries to finance loans use deposits. This master thesis seeks to determine the relationship between the credits and deposits of the Loreto financial system after the Covid 19 pandemic, in the 2020 period. With this objective, the present investigation of Quantitative type, Correlational level and Non-Experimental design. The research concludes that there is a direct relationship between the deposits and credits of the Loreto financial system in 2020, since the Correlation Coefficient was r = 0.877967384 and a Determination Coefficient of R2 = 0.770826727; demonstrating statistical significance between the independent variable (deposits) and the independent variable (credits). Likewise, loans maintained an egalitarian trend throughout 2020, amounting to an average monthly balance of S /. 2,665.58 million, with an average monthly variation of 0.07%; demonstrating that the measures applied by the Covid 19 pandemic have not affected them. In the same way, the deposits of the financial system, far from decreasing due to an alleged run and inability to save by the agents, have been moderately increased by a monthly average of 2.69%, equal to the average balance of S /. 1,834.33 million. The delinquency rate remained below 10%; showing an average variation of 7.43%.